Pengaruh Hambatan Samping terhadap Kinerja Jalan di Koridor Jalan Raya Utama Tengah Weleri - Elsa Rinawty Siregar; Intan Muning Harjanti; Bintang Septiarani (Teknik PWK (Perencanaan Wilayah Kota), 2021)
Side barriers have an effect on road performance in the Main Highway Corridor Tengah Weleri based on calculations using multiple linear regression analysis tools. It was found that busy hours occurred on Monday afternoon at 12.00-13.00 in office breaks and school children with a traffic volume of 2,152 pcu / hour, although the value of the net capacity is still relatively large, namely 6,148 pcu / hour so that the road performance in the corridor of Central Main Highway Weleri has a value of 0.35 which is classified as B with the current condition which is still stable but the speed is limited. This speed limitation is in fact influenced by the presence of pedestrians by 2% and vehicles that stop / park by 1% so that it disrupts traffic flow. This was found based on the results of the multiple linear regression equation obtained, namely Y = 0.117 - 0.002 X1 + 0.001 X2 + X3 - 0.004 X4. So it can be concluded that the level of road service in the corridor of Jalan Raya Utama Tengah Weleri can be increased to A with a road performance value of 0.117 if the side barriers are zero or none, because it is found that road performance in the corridor of Jalan Raya Utama Tengah Weleri is influenced by side friction of 93.6% simultaneously